6-Methoxyflavone targets SLC1A5 to induce ferroptosis in HeLa cells - Chaihong Zhang; Lihong Chen (PLoS ONE, 2025)
Objective This study aimed to explore the role and molecular mechanism of 6-methoxyflavone in inducing ferroptosis in HeLa cells. Methods Transmission electron microscopy (TEM), mitochondrial superoxide, and glutathione content assay were used to detect the effects of 6-methoxyflavone on ferroptosis. Tandem mass tag and parallel reaction monitoring proteomics, non-targeted and targeted metabolomics, polymerase chain reaction (qPCR), western blot, alternative splicing, new transcript, functional domain, molecular docking, non-covalent interaction, loss-of-function genetic manipulation, and mitochondrial superoxide analyses were performed to explore the molecular mechanism of 6-methoxyflavone-induced ferroptosis in HeLa cells. Results 6-Methoxyflavone induced ferroptosis in HeLa cells. Multi-omics, qPCR, western blot, alternative splicing, new transcript, functional domain, molecular docking, non-covalent interaction, loss-of-function genetic manipulation, and mitochondrial superoxide analyses indicated that 6-methoxyflavone induced ferroptosis in HeLa cells by upregulating the expression levels of SLC1A5 and mitochondrial superoxide. Molecular docking analyses showed that 6-methoxyflavone had the strongest affinity for SLC1A5. Non-covalent interaction analyses suggested that the interaction between 6-methoxyflavone and SLC1A5 was primarily driven by hydrophobic interactions. 6-Methoxyflavone targeted the peptide segment sequence LGPEGELLIR of SLC1A5. Conclusion 6-Methoxyflavone induced ferroptosis in HeLa cells by markedly altering ferroptosis-related genes, proteins, and metabolites expression, thereby exerting anti-cancer effects. The core gene responsible for the induction of ferroptosis and the upregulation of mitochondrial superoxide in HeLa cells by 6-methoxyflavone is SLC1A5.